What great brands do The Seven Brand-Building Principles that Separate the Best from the Rest - Denise Lee Yohn (San Francisco, CA Jossey-Bass, a Wiley brand, 2014)
Discover proven strategies for building powerful, world-class brands in this 800CEOREAD bestseller It's tempting to believe that brands like Apple, Nike, and Zappos achieved their iconic statuses because of serendipity, an unattainable magic formula, or even the genius of a single visionary leader. However, these companies all adopted specific approaches and principles that transformed their ordinary brands into industry leaders. In other words, great brands can be built--and Denise Lee Yohn knows exactly how to do it. Delivering a fresh perspective, Yohn's What Great Brands Do teaches an innovative brand-as-business strategy that enhances brand identity while boosting profit margins, improving company culture, and creating stronger stakeholder relationships. Drawing from twenty-five years of consulting work with such top brands as Frito-Lay, Sony, Nautica, and Burger King, Yohn explains key principles of her brand-as-business strategy.
Includes bibliographical references and index.
Keywords: Leadership